2017
DOI: 10.1108/jsbed-02-2017-0035
|View full text |Cite
|
Sign up to set email alerts
|

The impact of personal attitudes on the growth ambitions of small business owners

Abstract: Purpose The purpose of this paper is to provide an empirical evidence in support of widespread calls for new approaches to understanding small business growth, by exploring the use of non-positivist methods (e.g. critical realism) to analyse how owners’ innate dispositions shape growth in practice. Design/methodology/approach In 2014, a telephone survey was used to inform two focus groups and 29 in-depth interviews with small business owners throughout England, covering attitudes towards growth, the use of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Previous research has shown that some small-business owners are hesitant to increase their business. For instance, a lack of ownership control, increased financial risks and a heavier workload have been perceived as negative consequences with business growth (Davidsson 1989;Braidford et al 2017). Previous research also shows that high job demands are prevalent among small-business owners' and that high demands may be especially pronounced among individuals who owns larger businesses (Nordenmark et al 2012;Warr 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that some small-business owners are hesitant to increase their business. For instance, a lack of ownership control, increased financial risks and a heavier workload have been perceived as negative consequences with business growth (Davidsson 1989;Braidford et al 2017). Previous research also shows that high job demands are prevalent among small-business owners' and that high demands may be especially pronounced among individuals who owns larger businesses (Nordenmark et al 2012;Warr 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Wide variety of factors that potentially influence firm growth range from entrepreneur's characteristics, firm characteristics (Abdul Wahab & Al-Damen, 2015) to issues related to the institutional localities in which the business functions (Isaga, 2018). However, findings on these factors have generally been inconclusive (Isaga, 2018) probably because operations of small businesses particularly for developing economies are complicated by variety of factors, and as a result, no extensive surveys are conducted that comprehensively explain all the variables (Braidford, Drummond, & Stone, 2017). Perhaps, it may also suggest, as we propose, that the dominant use of non-financial proxies such as customer satisfaction, corporate reputation, happiness, personal development, cultural, and social network (see Mohamad Radzi et al, 2017) to proxy firm performance or growth is fairly limited.…”
Section: Introductionmentioning
confidence: 99%
“…, 2008; Mas-Tur and Ribeiro Soriano, 2014; Romero and Martínez-Román, 2012). In fact, the characteristics of the entrepreneur are a key element for the success of a firm, especially in its start-up phase (Braidford et al. , 2017; Del Bosco et al.…”
Section: Literature Reviewmentioning
confidence: 99%